2022
DOI: 10.3390/jcm11113077
|View full text |Cite
|
Sign up to set email alerts
|

Improving Cardiovascular Outcomes: The Era of Personalized Therapy in Atherosclerosis

Abstract: Data from the European Society of Cardiology report that cardiovascular disease (CVD) is responsible for app [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…In elderly patients, the following are observed more often: inferior wound healing, bleeding and thromboembolic events, renal complications, a more difficult return to daily activities, deterioration of cognitive functions and dementia, presence of chronic diseases, and frailty syndrome. All of these factors increase the risk associated with interventional procedures as well as complications in the post-operative period [ 73 , 74 , 75 , 76 , 77 ].…”
Section: The Faces Of Atherosclerosismentioning
confidence: 99%
“…In elderly patients, the following are observed more often: inferior wound healing, bleeding and thromboembolic events, renal complications, a more difficult return to daily activities, deterioration of cognitive functions and dementia, presence of chronic diseases, and frailty syndrome. All of these factors increase the risk associated with interventional procedures as well as complications in the post-operative period [ 73 , 74 , 75 , 76 , 77 ].…”
Section: The Faces Of Atherosclerosismentioning
confidence: 99%
“…Halting the progression of atherosclerotic lesions is the best indicator of treatment effectiveness [ 27 , 28 , 29 , 30 , 31 ]. Statins, angiotensin-converting enzyme inhibitors (ACEIs), angiotensin receptor blockers (ARBs), and calcium channel antagonists (amlodipine) have all been shown to slow the growth of atherosclerotic lesions [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Pharmacological Interventions That Decelerate or Cause Regre...mentioning
confidence: 99%
“…The risk of bleeding is even greater in the elderly. Studies have shown that even low doses of rivaroxaban have a stronger anticoagulant effect in elderly patients (median age 83 (75-87) years) compared to younger patients (median age 30 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) years) [108]. This is due to a prolonged prothrombin time, reduced activity of coagulation factors II and X, and reduced thrombin activation.…”
Section: Antiplatelet and Anticoagulant Drugsmentioning
confidence: 99%